LEARN2MOVE 0–2 years, a randomized early intervention trial for infants at very high risk of cerebral palsy: family outcome and infant's functional outcome. Issue 26 (17th December 2020) - Hielkema, Tjitske; Boxum, Anke G.; Hamer, Elisa G.; La Bastide-Van Gemert, Sacha; Dirks, Tineke; Reinders-Messelink, Heleen A.; Maathuis, Carel G. B.; Verheijden, Johannes; Geertzen, Jan H. B.; Hadders-Algra, Mijna
Abstract: Purpose: To compare family and functional outcome in infants at very high risk of cerebral palsy, after receiving the family centred programme "Coping with and Caring for infants with special needs (COPCA)" or typical infant physiotherapy. Materials and methods: Forty-three infants at very high risk were included before 9 months corrected age and randomly assigned to one year COPCA ( n = 23) or typical infant physiotherapy ( n = 20). Family and infant outcome were assessed before and during the intervention. Physiotherapy intervention sessions were analysed quantitatively for process analysis. Outcome was evaluated with non-parametric tests and linear mixed-effect models. Results: Between-group comparisons revealed no differences in family and infant outcomes. Within-group analysis showed that family's quality of life improved over time in the COPCA-group. Family empowerment was positively associated with intervention elements, including "caregiver coaching." Conclusions: One year of COPCA or typical infant physiotherapy resulted in similar family and functional outcomes. Yet, specific intervention elements, e.g., coaching, may increase empowerment of families of very high risk infants and may influence quality of life, which emphasizes the importance of family centred services. Implications for rehabilitation: One year of the family centred programme "Coping with and a Caring for infants with special needs" compared with typical infant physiotherapy resulted in similar family outcome and similar functional outcome for the infants at very high risk for cerebral palsy. Specific contents of intervention, such as caregiver coaching, are associated with more family empowerment and increased quality of life. Emphasis on family needs is important in early intervention for infants at very high risk for cerebral palsy.